Poly[bis[μ3-2-(1H-tetrazol-1-yl)acetato]cadmium(II)] - Li-Xia Xie (Acta Crystallographica Section E, 2009)
In the title compound, [Cd(C3H3N4O2)2]n, the CdII ion, located on a twofold rotation axis, is six-coordinated by two N atoms [Cd—N = 2.368 (2) Å] and four O atoms [Cd—O = 2.300 (1) and 2.260 (1) Å] from six 2-(1H-tetrazol-1-yl)acetate (L) ligands in a distorted octahedral geometry. The metal centres are connected via the tridentate L ligands into a three-dimensional polymeric structure.